Larval energetics of the Sydney rock oyster Saccostrea glomerata and Pacific oyster Magallana gigas - Gibbs, M; Scanes, E; Parker, L; Byrne, M; O'Connor, W; Virtue, P; Ross, P (Inter-Research Science Center, 2021)
© Inter-Research 2020. Larvae are a critical dispersal stage of marine invertebrates, and their survival depends on nutrition and energetics. This study compared the size, survival, metabolic rate and egg and larval lipid class profiles of larvae of the endemic Sydney rock oyster Saccostrea glomerata and the invasive Pacific oyster Magallana gigas through a period of starvation for 5 and 9 d after fertilisation. Starved larvae grew without food until 5 d of age, at which point they stopped developing, but resumed growth when fed. Egg lipids profiles comprised 78.1 and 74.5% triacylglycerol for M. gigas and S. glomerata respectively. When fed, larvae of M. gigas were significantly larger in size and had faster growth and similar survival compared to S. glomerata. When starved, larvae of M. gigas and S. glomerata grew at similar rates, and there was a trend for lower survival of M. gigas. Larval endogenous lipid reserves were deleted in the first 24 h. Larvae of M. gigas had more total lipids and comparatively more diacylglycerols, monoacylglycerols, phospholipids and cholesterol, whereas S. glomerata had more diacylglycerols and produced sterol esters. Starvation altered the patterns of lipid assimilation, and metabolic rates of larvae of M. gigas and S. glomerata differed over time. When starved, S. glomerata larvae had greater capacity to cope with starvation compared to M. gigas, perhaps due to an evolutionary history in oligotrophic estuaries. As the climate rapidly changes in this global climate-change hotspot, S. glomerata is likely to be negatively affected.